Privatisation and corporate governance in Kazakhstan and Uzbekistan: insights from a corporate survey in food and light industries - Manuela Troschke; Andreas Zeitler (Osteuropa-Institut München, 2006)
This paper presents the results from a private sector survey among companies of the food industry in Kazakhstan and Uzbekistan as well as of the light industry in Uzbekistan. It provides microeconomic evidence on the change in the companies' ownership structure resulting from the privatisation programmes as well as the development in more recent years. The privatisation of companies was more profound in Kazakhstan than in Uzbekistan where the state still retained larger shares in its companies and even managed to re-increase its stakes due to strategic considerations. While the data confirm and prove the extent of the insider privatisation in Kazakhstan, Uzbek companies' ownership got more dispersed and company insiders play a very subordinate role. The use and design of manager contracts in these two countries does not turn out to feature basic incentive components on a broad scale as in the case of the Chinese management contracts contradicting the hypotheses of a similar application in Uzbekistan's de facto state enterprises. Company control was highly transferred into the responsibility of corporate bodies in both countries though state interference in the companies' affairs remains an important aspect of doing business, especially in Uzbekistan. The companies face further obstacles which hinder and retard the development of a sound private corporate sector, especially a high tax burden and bureaucratic red tape, macroeconomic instability, lack of finance and an inadequate provision of infrastructure. The state, especially in Uzbekistan, still intervenes in the private sector in favour of selected companies which improves these companies' perception about the role of the state. On the other hand, this state behaviour prevents or at least delays the dissolution of the inherited structural and corporate distortions which would improve corporate efficiency and would be essential for a successful transition to a market economy.
Keywords: 330